A Theory of Commodity Price Fluctuations - Chambers, Marcus J.; Bailey, Roy E. (Journal of Political Economy, 1996)
This paper studies the price fluctuations of storable commodities that are traded in open markets and are subject to random shocks to demand or, more particularly, to supply. It relaxes the common assumption that the shocks are identically and independently distributed in favor of temporally dependent and periodic disturbances. The existence of a unique stationary rational expectations equilibrium is demonstrated for each of the models analyzed and testable implications of the models are derived. An illustrative empirical investigation is then undertaken for the model with periodic disturbances using monthly time-series observations for seven commodities over the period 1960-93. Copyright 1996 by University of Chicago Press.